Mediação oral da literatura: a voz do bibliotecário lendo ou narrando - Bortolin, Sueli [UNESP] (2010)
This thesis aimed to construct the concept of Oral Mediation of Literature. This theory was proposed having as a starting-point the researcher's perception that the library and the librarian engage little with the reading practices in their multiple languages. It argues that the librarian, besides worrying about organizing printed or networked information, should take initiatives that leaded the reader to the appropriation of the information through reading. The bibliographic research was the method chosen for the development of this research; approaching areas such as Arts, Performing Arts, Communication, History, Literature and Pedagogy the researcher exceeded the limits of Librarianship. This option enabled the creation of concepts like oralisfera, oralistologia, listener-reader, narrator-reader and principally of Oral Mediation of Literature. Therefore, the intention is to bring subsidies that lead the librarians to promote new and diverse activities that involve orality and, hence, the reception aesthetics, literary mediation and the oral narrative using the voice, body, space and presence, that were approached in this paper. Thus, it is hoped that the ideas and proposals presented here may be useful to expand the use of libraries and their respective collections through literary, social, cultural, educational and scientific activities